Modulation of adenylyl cyclase activity in young and adult rat brain cortex. Identification of suramin as a direct inhibitor of adenylyl cyclase - Stöhr, Jiří; Novotný, Jiří; Bouřová, Lenka; Svoboda, Petr (Journal of cellular and molecular medicine, 2005)
Adenylyl cyclase (AC) in brain cortex from young (12-day-old) rats exhibits markedly higher activity than in adult (90-day-old) animals. In order to find some possibly different regulatory features of AC in these two age groups, here we modulated AC activity by dithiothreitol (DTT), Fe(2+), ascorbic acid and suramin. We did not detect any substantial difference between the effects of all these tested agents on AC activity in cerebrocortical membranes from young and adult rats, and the enzyme activity was always about two-fold higher in the former preparations. Nevertheless, several interesting findings have come out of these investigations. Whereas forskolin- and Mn(2+)-stimulated AC activity was significantly enhanced by the addition of DTT, increased concentrations of Fe(2+) ions or ascorbic acid substantially suppressed the enzyme activity. Lipid peroxidation induced by suitable combinations of DTT/Fe(2+) or by ascorbic acid did not influence AC activity. We have also observed that PKC- or protein tyrosine kinase-mediated phosphorylation apparently does not play any significant role in different activity of AC determined in cerebrocortical preparations from young and adult rats. Our experiments analysing the presumed modulatory role of suramin revealed that this pharmacologically important drug may act as a direct inhibitor of AC. The enzyme activity was diminished to the same extent by suramin in membranes from both tested age groups. Our present data show that AC is regulated similarly in brain cortex from both young and adult rats, but its overall activity is much lower in adulthood.
Keywords: Animals; sloučeniny hliníku; Adenylyl Cyclases; guanosin 5'-O-(3-thiotrifosfát); Dose-Response Relationship, Drug; Dithiothreitol; Phosphorylation; tyrosinkinasy; potkani Wistar; kolforsin; proteinkinasa C; Lipid Peroxidation; Adenylyl Cyclase Inhibitors; Iron; financování organizované; Colforsin; zvířata; buněčná membrána; Fluorides; Aluminum Compounds; mozková kůra; peroxidace lipidů; Aging; Suramin; adenylátcyklasy; Protein-Tyrosine Kinases; fluoridy; mozek; Financing, Organized; stárnutí; kyselina askorbová; časové faktory; Guanosine 5'-O-(3-Thiotriphosphate); vztah mezi dávkou a účinkem léčiva; Ascorbic Acid; Time Factors; Rats; mangan; Male; dithiothreitol; Rats, Wistar; železo; Brain; Cell Membrane; suramin; Cerebral Cortex; Manganese; krysa rodu Rattus; Protein Kinase C; inhibitory adenylylcyklasy; mužské pohlaví; fosforylace